The dynamics of the stress response markers in uterine artery embolization - Dmitriy V. Khabarov; Irina P. Siutkina; Elena G. Koroleva; Alexander A. Smagin; Marya V. Kochetkova; Alexander Y. Demura (Бюллетень сибирской медицины, 2017)
Aim. To estimate immunobiochemical markers of the stress response during uterine artery embolization (UAE), and to assess the connection of the endocrine and immune response with pain severity Materials and мethods: 62 patients (ages 31 to 56) with a diagnosis of multiple symptomatic uterine body fibroids were made EMA, and analgesia was achieved by intravenous injection of narcotic and non-narcotic analgesics. Immunobiochemical profile of the stress reaction was investigated (IL-1, IL-6, TNFα, IL-4, IL-10, C-reactive protein (CRP), adrenocorticotropic hormone (ACTH), cortisol, blood glucose) at four (I ONLY SEE 3-SMT) time points (baseline at 2 hours after occlusion of the uterine arteries, and 24 and 48 hours after surgery). Pain syndrome was assessed using a visual analogue scale (VAS) by means of hemodynamic profile.Results. The occlusion of the uterine arteries and ischemia myoma nodes lead to the development of the stress response, as anincrease in the serum concentration of pro-inflammatory (IL-1, IL-6, TNFα) and anti-inflammatory (IL-4, IL-10) cytokines, CRP, stress hormones (ACTH, cortisol) levels of glucose was observed. Pain of various intensity was recorded in all cases, and 18% of patients experienced marked pain (7 to 10 points on the VAS).Conclusion. The maximum increase in immunobiochemical stress markers coincides with the highest manifestations of pain. The necessity of optimization methods of analgesia when performing EMA with the use of immunobiochemical stress markers as a control reaction taking into account hemodynamic profile and VAS data was observed.